Facile TEMPO Immobilization onto Poly(acrylic acid)-Modified Magnetic Nanoparticles: Preparation and Property - Ma, Huiqing; Bei, Yiling; Liu, Xiaoxuan; Huang, Guohui (International Journal of Polymer Science, 2017)
Adding catalysts to magnetic polyvalent supports facilitating catalyst recycling and recovery seems feasible. Polymer-modified magnetic nanocomposites for organocatalyst immobilization are a plausible approach to this technology. Here, we present facile and efficient method for 2,2′,6,6′-tetramethylpiperidinyl-1-oxy (TEMPO) immobilization onto polymer-modified magnetic nanoparticles under mild reaction conditions. Poly(acrylic acid) was chosen to graft from magnetic nanoparticle through a simple inverse emulsion polymerization technique. The resulting poly(acrylic acid) magnetic nanocomposite is an ideal material to immobilize the organocatalyst 4-hydroxy-2,2′,6,6′-tetramethylpiperidinyl-1-oxy (H-TEMPO) via an esterification reaction with pendant carboxyl group on the polymer chain. Instrumental analysis confirmed that poly(acrylic acid) chain was grafted on the silica-coated magnetic particles by this simple method while maintaining their magnetic properties; elemental analysis indicated that TEMPO was efficiently immobilized onto the polymer chain. The catalysis tests under both Anelli and Minisci system showed that the nanocomposite catalyst exhibits proper selectivity and activity for the alcohol/aldehyde transformation. Recycling experiments showed that stability and reusability of the nanocomposite catalyst were satisfying.